METODOLOGI DAN KRITERIA KRISTOLOGI - Fitriani Fitriani; Joan Amazia; Swinarti Swinarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines Christological methodology and criteria using a qualitative approach with systematic literature review method. The research traces the development of Christological thought from the patristic era to contemporary times by analyzing primary and secondary theological sources. The analytical methods employed include content analysis to identify methodological patterns and critical analysis to evaluate theological argumentation consistency. The findings reveal that a comprehensive Christological approach must integrate historical-existential dimensions, dogmatic frameworks, and cultural contextualization. The study highlights three essential criteria: fidelity to Christian tradition, contextual relevance, and philosophical-theological coherence.